Influence of podcasts characteristics on higher students’ acceptance - Carvalho, Ana Amélia Amorim (2008)
Podcasts are a new way to deliver audio information. They have been used in several universities. The study reported in this paper describes four types of podcasts of different length used in four courses. It focuses on students’ acceptance of podcasts types and length in their courses. Results show their preference for short podcasts, and their interest in having podcasts in other courses. The teachers also recognized its impact in their courses. However some students prefer written information instead of a podcast, as they can underline and annotate it. Further research is needed to clarify this aspect but also to relate types of podcasts and the use of mobile devices, as well as the implications of podcasts in distance learning to diminish the transactional distance.